ANALISIS KEMAMPUAN INTERAKSI SOSIAL ANAK BERKEBUTUHAN KHUSUS DIKELAS INKLUSI SEKOLAH DASAR ISLAMIC GLOBAL SCHOOL BANDUNGREJOSARI MALANG - Dewi Khalimatul Mursyidah; Rosichin Mansur; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The purpose of this study is 1) to know and explain the ability of social interaction of children who have special needs with their environment in inclusive classrooms, 2) to find out how children with special needs interact socially with others in the surrounding environment, and 3 ) knowing how teachers interact with children with special needs and instilling a culture of obedience in worshiping their students in the inclusion of the Bandungrejosari Islamic Global School in Malang. So the qualitative descriptive approach method is used. The research subjects were a number of students with special needs, Special Friends Teachers (GPK), and classmates in the inclusive class of the Bandung Islamic Global School of elementary school Malang. Data collection uses observation and interviews, to observe how the conditions of each subject. The findings of the researchers were that subject 1 was subject 2 even though they both had emotional disorders but the level of ability of social interaction varied. The way to greet a new person is to call his name directly. If interacting, subjects tend to put their faces flat and look in the other direction. can respond to calls if the other person is calling repeatedly. GPK always strives to improve learning and improve learning activities in inclusive classes both in improving academic and social learning so that it becomes better learning and progress for child with needed specialKeywords: social interaction ability, children with special needs